Identification of genes controlling fruit shape in Thai pumpkin (Cucurbita moschata Duch.) - Ketsakul, S.; Imsabai, W.; Tangtrakulwanich, K.; Auvuchanon, A. (International Journal of Agricultural Technology, 2020)
The genetic control of fruit shape in pumpkins was determined in the fields during 2015 and 2017. The breeding design consisted of seven crosses derived from inbred pumpkin lines. The parents originated from Thai landrace cultivars maintained by continuous selfing at Kasetsart University, Kamphaeng Saen Campus, Nakhon Pathom, Thailand. Different qualitative characters of fruit shapes of parents were chosen, including three elongated, two flattened and two globular shaped lines. The fruit shape and length/width (L/W) ratio of all parents and derived cross-progenies (F1 and F2) were evaluated. The results showed that all genotypes controlling the fruit shape hypotheses resulted from the influence of three genes. The genotype Ff, Gg, and Ee resulted in a globular fruit shape, whereas ff, gg, and ee led to an elongated shape. A flattened shape was controlled by FF, GG, and EE. In terms of gene action, the results supported ee dominance over ffG- and F-gg. The elongated shape phenotype was due to the action of ffggee, ffG-ee, and F-ggee genes. This research suggests that the analysis of fruit shape using the L/W ratio could be a useful approach for selecting other characteristics of pumpkin shapes.